THE ROLE OF DIGITAL TOOLS IN ENHANCING VOCABULARY ACQUISITION FOR A2 LEARNERS - Davronbek Komiljonov, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines the effectiveness of digital tools in vocabulary acquisition for learners at the A2 level according to the Common European Framework of Reference for Languages (CEFR). Drawing on an extensive review of empirical and theoretical  research,  the  study  highlights  the  role  of  mobile  applications,  spaced repetition  flashcards,  multimedia  resources  such  as  captioned  videos,  game-based learning, and adaptive AI-driven platforms in facilitating vocabulary development. The results demonstrate that digital tools significantly improve vocabulary retention and learner motivation when properly integrated into pedagogical practices. The article emphasizes the necessity of teacher mediation, the importance of multimodal learning strategies,  and  the  need  for  long-term  empirical  research  with  CEFR-specific participant  samples.  Recommendations  for  pedagogical  practice  and  directions  for future inquiry are provided.